It´s all said in music: The Presence of Romantic Aesthetic in the Musical Press of Buenos Aires (1837-1838) - Guillamón, Guillermina (2016)
This work strides to analyze the social and aesthetics function attributed to music in the newspaper Boletín Musical (1837) and La Moda (1837-1838). The hypothesis guiding the article states that using the romanticism as a paradigm of thought, the newspaper built music as an inclusive practice, available to all the people, thought, by the new romantic generation, as the recipient of a civilizatory program. Discussing many of the assumptions of the Enlightenment, as a tradition that they considered outdated, what they were really doing was questioning the cultural politics of the previous government and, derived from it, affirm their support for the current governor, Juan Manuel de Rosas.